2004
DOI: 10.1038/sj.embor.7400067
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of the overlapping functions of DnaK and trigger factor

Abstract: Trigger factor (TF) is a ribosome-bound protein that combines catalysis of peptidyl-prolyl isomerization and chaperone-like activities in Escherichia coli. TF was shown to cooperate with the DnaK (Hsp70) chaperone machinery in the folding of newly synthesized proteins, and the double deletion of the corresponding genes (tig and dnaK) exhibited synthetic lethality. We used a detailed genetic approach to characterize various aspects of this functional cooperation in vivo. Surprisingly, we showed that under speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
182
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(195 citation statements)
references
References 32 publications
(58 reference statements)
12
182
0
1
Order By: Relevance
“…Furthermore, it appears that the conformational change of the extended signature motif plays a key role in facilitating TFa docking on the 50S subunit. Consistently, a recent biochemical report has indicated that mutations and even deletion of the TF signature motif exert only a mild effect on TF function, compared with the complete deletion of the N-terminal domain (22). As association with the ribosome is a prerequisite for TF chaperone activity (23), the interactions of helix A2 with L29 and the C terminus of L23 seem to contribute significantly for TF binding.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, it appears that the conformational change of the extended signature motif plays a key role in facilitating TFa docking on the 50S subunit. Consistently, a recent biochemical report has indicated that mutations and even deletion of the TF signature motif exert only a mild effect on TF function, compared with the complete deletion of the N-terminal domain (22). As association with the ribosome is a prerequisite for TF chaperone activity (23), the interactions of helix A2 with L29 and the C terminus of L23 seem to contribute significantly for TF binding.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, we reported that of many other known chaperone and protease genes tested, only GroEL͞GroES overproduction could provide enough assistance to support growth of our ⌬tig ⌬dnaKdnaJ strain as well as prevent aggregation under these conditions (9). Therefore, it is conceivable that TF, DnaK, GroEL, and SecB may compete for the same pool of both secretory and cytosolic proteins, although with a considerable advantage for TF, being more abundant and localized near the ribosome exit channel (28).…”
Section: Discussionmentioning
confidence: 99%
“…To answer this question, we took advantage of a previously described mutation in secB (resulting in the E77K amino acid substitution in the SecB protein), which Fresh transformants were then grown for 24 h at 20°C in LB-ampicillin, serially diluted, and spotted on LB-ampicillin agar plates without (Ϫ) or with (ϩ) 2 mM IPTG inducer at the indicated temperatures. Note that TF overproduction is toxic in the ⌬tig ⌬dnaKdnaJ triple mutant, as described (9).…”
Section: Secb Overexpression Suppresses Intracellular Protein Aggregamentioning
confidence: 99%
See 1 more Smart Citation
“…Transposon mutagenesis analysis predicts that dnaK is also essential for growth in Mtb (14,15). In contrast, DnaK is nonessential in other bacteria studied, such as Escherichia coli, where its functions are redundant with those of trigger factor (encoded by tig), such that dnaK and tig form a synthetic lethal pair (16)(17)(18). In mycobacteria, the repressor HspR negatively regulates the heat shock response and is encoded in the same operon as dnaK (Fig.…”
mentioning
confidence: 99%